2011
DOI: 10.1111/j.1524-475x.2011.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of silver dressings and antibiotics on MRSA and MSSA isolated from burn patients

Abstract: In this study our objectives were (1) to investigate whether meticillin-resistant Staphylococcus aureus (MRSA) showed an increased tolerance to silver wound dressings compared with meticillin-sensitive S. aureus (MSSA); and (2) to evaluate the effects of bacterial phenotypic states of MRSA and MSSA, and pH, on the activity of silver wound dressings and two antibiotics, ampicillin and clindamycin. Twenty MRSA strains and 10 MSSA strains isolated from burns patients in South Africa were evaluated for their susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…44 In this study the objectives were to investigate whether MRSA demonstrated an increased tolerance to silver wound dressings compared with MSSA and to evaluate the effects of bacterial phenotypic states of MRSA and MSSA, and pH, on the activity of silver wound dressings and two antibiotics, ampicillin and clindamycin. Twenty MRSA and 10 MSSA isolates from burns patients in South Africa were evaluated for their susceptibility to a silver alginate and a silver carboxy methyl cellulose wound dressing, employing a CZOI assay, conducted on Mueller Hinton agar (MHA) and a poloxamer-based biofilm model.…”
Section: Efficacy Of Silver On Biofilmsmentioning
confidence: 99%
“…44 In this study the objectives were to investigate whether MRSA demonstrated an increased tolerance to silver wound dressings compared with MSSA and to evaluate the effects of bacterial phenotypic states of MRSA and MSSA, and pH, on the activity of silver wound dressings and two antibiotics, ampicillin and clindamycin. Twenty MRSA and 10 MSSA isolates from burns patients in South Africa were evaluated for their susceptibility to a silver alginate and a silver carboxy methyl cellulose wound dressing, employing a CZOI assay, conducted on Mueller Hinton agar (MHA) and a poloxamer-based biofilm model.…”
Section: Efficacy Of Silver On Biofilmsmentioning
confidence: 99%
“…A variety of silver forms exist are powders, foams, hydrocolloids, hydrogels, polymeric films and meshes. When in solution, reactive silver ions (Ag + ) are formed and induce toxicity to many of the structural components of the bacterial cell wall, and biochemical pathways such as the respiratory cytochromes, and DNA and RNA alterations to prevent transcription and cellular division (30). The results are more complex for the members of the staphylococcal group that remain a significant contributor to chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is little evidence for the development of silver resistance; so we investigated the potential of combining a biofilm disrupting technology with a chemical silver treatment. Experimental work by KCI (27) has shown a consistent release of non-ionic silver particles from the silver foam for the first 72 hours (29). We, therefore, compared the efficacy of silver foam and black foam with and without concurrent TNP treatment at 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Silver plays an important role in the management of burn wounds by reducing the microbial growth within a wound dressing and wound bed. The antimicrobial properties of silver-impregnated wound dressings against Gram-positive and Gram-negative bacteria have been demonstrated in several in vivo studies [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%